If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 66 = 7x + -4 Reorder the terms: 66 = -4 + 7x Solving 66 = -4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 66 + -7x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 66 + -7x = -4 + 0 66 + -7x = -4 Add '-66' to each side of the equation. 66 + -66 + -7x = -4 + -66 Combine like terms: 66 + -66 = 0 0 + -7x = -4 + -66 -7x = -4 + -66 Combine like terms: -4 + -66 = -70 -7x = -70 Divide each side by '-7'. x = 10 Simplifying x = 10
| 4m^2=9m-9 | | 17+s=152 | | 18=5y+3(y-2) | | 38=4(v+2)+6v | | 0=-3.5x+1 | | 5(2x-1)-(10x-7)=-8 | | 7x^2-3x=3 | | 13x-42=2x | | Y/8=68 | | 2x2/3-5=3 | | 2x2/3-6=3 | | 15x+8y+2xy=0 | | 0.22(x+8)=0.2x+3.2 | | 2x^2+8x-25=0 | | (x^2-2)(x+4)= | | 7-(6-8x)=4x+2 | | 4/x-6=-11/5 | | 4y+92=169 | | -4/9x=3/4 | | (3w/4)=5w-102 | | (3p/4)=6p-189 | | sinx/cosy=0 | | 13-5y=7x | | 6x^2=-9x-1 | | (2a/3)=6a-112 | | 7x^2(x+3)= | | 0=-552 | | 4p-65=(3p/4) | | (2p/3)=3p=35 | | (10-g)/-2=7 | | 18m=418 | | -9.6+2w=3.2 |